2007
DOI: 10.1029/2006ja012184
|View full text |Cite
|
Sign up to set email alerts
|

Particle and field characteristics of broadband electrons observed by the FAST satellite during a geomagnetic storm

Abstract: [1] Broadband electrons (BBEs) are remarkable flux enhancements (>10 13 eV cm À2 s À1 ) of precipitating electrons over a broad energy range (0.03-30 keV) near the equatorward edge of the auroral oval during geomagnetic storms. We show characteristics of particles (energy spectra and pitch angle distribution) and fields (electric field, magnetic field, and wave spectra) during a BBE event observed by the Fast Auroral SnapshoT (FAST) satellite. The BBEs were observed at an altitude of $2000 km at 59°-61°i nvari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…They generally occur (1) in short‐lived bursts (1–2 s in time, or equivalently, about 14 km in space when observed by a moving platform) and (2) with the pitch angle highly field aligned [ Johnstone and Winningham , ]. However, broadband precipitation may persist longer than 1 min with a spatial scale of about 10 km [ Semeter et al , ] or for about 14 min with a spatial scale of about 200 km [ Nakajima et al , ]. The occurrence rate does not depend significantly on geomagnetic activity, at least between 2000 MLT and 0300 MLT [ Nagatsuma et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…They generally occur (1) in short‐lived bursts (1–2 s in time, or equivalently, about 14 km in space when observed by a moving platform) and (2) with the pitch angle highly field aligned [ Johnstone and Winningham , ]. However, broadband precipitation may persist longer than 1 min with a spatial scale of about 10 km [ Semeter et al , ] or for about 14 min with a spatial scale of about 200 km [ Nakajima et al , ]. The occurrence rate does not depend significantly on geomagnetic activity, at least between 2000 MLT and 0300 MLT [ Nagatsuma et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…These facts indicate that a substorm began at ∼0500–0600 MLTs at 1347–1349 UT. The BBEs occurred in association with the storm time substorm, which has been reported in previous studies of BBEs using the magnetic field data obtained in the geosynchronous orbit and on the ground [ Shiokawa et al , 1996; Nakajima et al , 2007, 2008]. In this study, we examined the plasma dynamics in the inner magnetosphere associated with the storm time substorm by using data obtained by DS TC1.…”
Section: Discussionmentioning
confidence: 73%
“…It is reasonable to speculate that the enhanced electron precipitation over the entire region results from the same mechanisms. In an event study of BBEs observed by FAST, Nakajima et al [2007] reported that simultaneous auroral images from the Polar satellite showed that the precipitating region of BBEs covered ∼10° in latitude and ∼1 h in local time, which included the ionospheric footprint of FAST.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major geomagnetic storms trigger a wide range of changes in the Earth's magnetosphere, inluding the transfer of a significant amount of energy, and are usually associated with coronal mass ejections, large interplanetary magnetic fields, and/or high-pressure solar wind plasma [Baker et al, 2001]. There are many unusual particle acceleration processes that can occur, including prompt energization of relativistic electrons in the radiation belts [Wygant et al, 1994], acceleration of electrons over a broad energy range in the auroral zone [Shiokawa et al, 1996;Dombeck et al, 2005;Nakajima et al, 2007], and strong outflow of ionospheric ions in the polar cap [Moore et al, 1999;Strangeway et al, 2000]. Although much of the research on storms in the auroral zone has focused on electrons, including those that produce subauroral red (SAR) arcs and great red aurora [Kozyra et al, 1993[Kozyra et al, , 1997Shiokawa et al, 1997], there are unusual signatures in the ions that are seen during large storms and which are sometimes coincident with these electron signatures.…”
Section: Introductionmentioning
confidence: 99%